2023
DOI: 10.3390/molecules28052021
|View full text |Cite
|
Sign up to set email alerts
|

Organo-Montmorillonite Modified by Gemini Quaternary Ammonium Surfactants with Different Counterions for Adsorption toward Phenol

Abstract: The discharge of industrial phenol pollutants causes great harm to the natural environment and human health. In this study, phenol removal from water was studied via the adsorption of Na–montmorillonite (Na–Mt) modified by a series of Gemini quaternary ammonium surfactants with different counterions [(C11H23CONH(CH2)2N+ (CH3)2(CH2)2 N+(CH3)2 (CH2)2NHCOC11H23·2Y−, Y = CH3CO3−, C6H5COO− and Br−, 12–2–12·2Y−]. The results of the phenol adsorption indicated that MMt–12–2–12·2Br−, MMt–12–2–12·2CH3CO3− and MMt–12–2–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This is because after modified by surfactant, Mt changes from hydrophilicity to hydrophobicity, and the interlayer spacing of OMt increases sharply, thereby improving the adsorption capacity of methyl orange. However, as the amount of modifier exceeds 2.0 CEC, the interlayer spacing of OMt hardly changes or even decreases, as shown in Table 1 33) . In addition, the additional surfactant molecules lead to a densely packed, and the active sites and interlayer space originally used for adsorption is occupied, thus reducing the adsorption capacity of methyl orange 25) .…”
Section: Effect Of the Amount Of Surfactant (Cec)mentioning
confidence: 95%
See 3 more Smart Citations
“…This is because after modified by surfactant, Mt changes from hydrophilicity to hydrophobicity, and the interlayer spacing of OMt increases sharply, thereby improving the adsorption capacity of methyl orange. However, as the amount of modifier exceeds 2.0 CEC, the interlayer spacing of OMt hardly changes or even decreases, as shown in Table 1 33) . In addition, the additional surfactant molecules lead to a densely packed, and the active sites and interlayer space originally used for adsorption is occupied, thus reducing the adsorption capacity of methyl orange 25) .…”
Section: Effect Of the Amount Of Surfactant (Cec)mentioning
confidence: 95%
“…1) were synthesized as described previously 31,32) . The preparation and characterization of the modified Na-Mt (OMt-12-2-12・2Y − ) was based on our previous study 33) . According to the CEC of Na-Mt, OMts modified under 0.4, 0.8, 1.2, 1.6, 2.0, 2.4, and 2.8 CEC modifier dosages were prepared.…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…During this period, the method of introducing magnetic particles to remove dyes was observed. In the current year, 2023, Wei et al [121], Xie et al [122], and Hu et al [123] reported on the removal of phenol by using modified clay. Wang et al [124], Zeng et al [125], and Nazarizadeh et al [126] reported heavy metal removal by modified organoclay.…”
Section: Water Pollutionmentioning
confidence: 99%